2022
DOI: 10.1021/acsami.2c07235
|View full text |Cite
|
Sign up to set email alerts
|

Low-Power Magnetic Resonance-Guided Focused Ultrasound Tumor Ablation upon Controlled Accumulation of Magnetic Nanoparticles by Cascade-Activated DNA Cross-Linkers

Abstract: Magnetic resonance-guided focused ultrasound (MRgFUS) is a promising non-invasive surgical technique with spatial specificity and minimal off-target effects. Despite the expanding clinical applications, the major obstacles associated with MRgFUS still lie in low magnetic resonance imaging (MRI) sensitivity and safety issues. High ultrasound power is required to resist the energy attenuation during the delivery to the tumor site and may cause damage to the surrounding healthy tissues. Herein, a surface modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Magnetic resonance-guided focused ultrasound surgery (MRgFUS) offers an effective opportunity for tumor ablation as a prospering non-invasive ultrasound thermal therapy method for soft tissue sites. 3,27 Due to high accumulation and a long retention time, STPSD nanoparticles become potential sensitizers for MRgFUS applications. The MRgFUS system can monitor the temperature of the tumor and surrounding area in real time via MRI.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance-guided focused ultrasound surgery (MRgFUS) offers an effective opportunity for tumor ablation as a prospering non-invasive ultrasound thermal therapy method for soft tissue sites. 3,27 Due to high accumulation and a long retention time, STPSD nanoparticles become potential sensitizers for MRgFUS applications. The MRgFUS system can monitor the temperature of the tumor and surrounding area in real time via MRI.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…MR-guided focused ultrasound surgery (MRgFUS), combined with intravenously injected contrast agents, has emerged as a noninvasive thermal ablation technology for essential tremor, uterine fibroids and some solid tumors. [1][2][3][4] However, therapeutic outcomes in oncology can be improved with the precision guidance of MRgFUS which offers real-time MRI feedback for tissue monitoring and intraoperative target location. 5 Magnetic resonance imaging (MRI) that provides precision diagnostics with a high degree of spatial and temporal resolution can be a clinically promising technique in MRgFUS ablation.…”
Section: Introductionmentioning
confidence: 99%
“…In the tumor area, the labile TK-PEG layer was shed off in response to overexpressed ROS, after which DNA folded in response to tumor acidity and drove nanoparticles’ aggregation, accumulating at the tumor site, thereby enhancing magnetic resonance imaging and ultrasound ablation (Fig. 6 c) [ 139 ]. Pharmacy Department and others also designed a pH and GSH dual response nanomedicines through surface modification.…”
Section: Nano-engineering In Tumor Treatmentmentioning
confidence: 99%
“…c Schematic diagram of the synthetic route of FSIC5P and the function of FSIC5P in response to ROS and pH in tumor tissues. Reproduced with permission [ 139 ]. Copyright 2022, American Chemical Society …”
Section: Nano-engineering In Tumor Treatmentmentioning
confidence: 99%
“…Pre- and post-MRI results indicated that HIFU permanently destroyed the tumor. 215 In 2022, Zhang et al 216 synthesized ferromagnetic Fe 3 O 4 nanoparticles with a diameter of 70 nm. The Fe 3 O 4 nanoparticles were coated onto silica after conjugation with i-motif DNA to prepare a Fe 3 O 4 @SiO 2 /i-motif.…”
Section: Ultrasound Therapy Based On Mnpsmentioning
confidence: 99%